Utilization of wild desert plant extracts for the in vitro control of gastrointestinal nematodes in cattle. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to evaluate the effects of plant extracts from desert species on egg-hatching inhibition (EHI) and larval mortality of gastrointestinal nematodes (GINs) in cattle under in vitro conditions. Materials and Methods: Hydro-alcoholic extracts of tasajillo [Cylindropuntia leptocaulis (DC) F.M. Kunth], coyonoxtle [Cylindropuntia imbricata (Haw) F.M. Kunth], mariola (Parthenium incanum Kunth), and mesquite [Neltuma juliflora (Sw.) Raf.] were tested. GIN eggs and infective larvae were exposed to the plant extracts in decreasing doses, and the median lethal dose50 (LD50) and maximum lethal dose99 (LD99) were calculated using the SAS PROBIT procedure. Results: The C. imbricata extract demonstrated the highest EHI at a small LD50 (2.31 mg/ml) and achieved 100% larval mortality at a 5.8 mg/ml concentration. The P. incanum extract showed the highest larval mortality at the LD99 (6.50 mg/ml), although N. juliflora had the lowest LD50. However, the N. juliflora pod extract was the least effective overall. These findings indicate that C. imbricata was the most effective extract for inhibiting egg hatching, while P. incanum was the most effective for promoting larval mortality under in vitro conditions. Conclusion: The small doses used against eggs and larvae of nematode parasites suggest that wild desert plants could provide a viable and ecological alternative for the in vitro control of GINs in cattle.J. Adv. Vet. Anim. Res., 12(2): 529–538, June 2025http://doi.org/10.5455/javar.2025.l917